Restraining Effects Of Mobile Wallet Payment Adoption: Coimbatore City - Dr. Gayathiry D; Dr. Poorna K (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2021)
Digital India is the flagship strategy of the Government of India. This proposal wasinitiated on 1st July 2015 by Prime Minister Mr.Narendra Modi, with an idea to transformIndia into a digitally authorized society and knowledge economy. Internet has wrapped upeveryone's imagination and still continues to go forward in India. There is a stable desireto keep tempo with internet trends. Further, there has been a rise in adoption of newtechnologies, embarrassment of digital street like M-Wallets etc., On 8thNovember 2017,the Government of India announced the demonetization of Rs. 500 and Rs. 1000 notes, tocontrol black money, corruption and terrorism. During 2015-16 to 2021-22, usage ofsmartphones and mobile internet access will lead to growth of e-commerce sector togetherwith increasing disposable of incomes. The study is based on 370 valid responses receivedthrough a structured questionnaire. Data collected was analyzed by using statistical toolslike Kruskal Wallis Test, One-Way Anova and Factors Analysis . Demonetization drive ofgovernment of India has contributed immensely towards awareness, usage and acceptanceof online payment.